P017 Fecal wash host transcriptomics identifies inflammation throughout the colon and terminal ileum. (30th January 2023) - Dan, S; Ungar, B; Ben-Moshe, S; Bahar Halpern, K; Yavzori, M; Fudim, E; Picard, O; Abitbol, C M; Harnik, S; Kopylov, U; Ben-Horin, S; Itzkovitz, S; et al.
Abstract: Background: Non-invasive modalities for assessing active endoscopic and histological inflammation in Crohn's disease and Ulcerative Colitis patients are critically needed. Fecal wash host transcriptomics has been shown to be a robust classifier of endoscopic and histological inflammation in inflammatory bowel disease (IBD) patients with distal colitis. Whether such fecal washes can inform on inflammatory processes occurring in more proximal intestinal segments is currently unknown. Methods: Crohn's disease and Ulcerative Colitis patients as well as healthy controls were prospectively enrolled. Host transcriptomes of biopsies and fecal washes obtained during colonoscopy at predefined locations throughout the colon and terminal ileum were analyzed and associated with same time-point clinical, endoscopic and histological parameters. Results: 59 IBD patients and 50 controls were prospectively enrolled. Biospies and fecal washes from the distal, proximal colon and terminal ileum were compared. We find that host transcriptomics of distal fecal washes robustly classify histological inflammation in ileal and proximal colonic Crohn's disease, even without distal colonic involvement. Receiver operating characteristic (ROC) curve analysis demonstrated significantly higher classification power based on the fecal wash transcriptomics compared to biopsies: Area Under the Curve, AUC=0.94+-0.07 for UC distal fecal washes and AUC=0.94+-0.09 for distal fecal washes of CD patients without distal colonic involvement, as compared to all distal biopsies AUC= 0.82+-0.20. We further demonstrate that fecal washes consist of modules of co-expressed immune, stromal and epithelial genes. Fecal wash expression of gene modules previously associated with lack of response to biological therapies correlates with disease severity. Figure 1 - Host transcriptomics of fecal washes from different intestinal segments captures information that is distinct from same – segment biopsy transcriptomics. A) Experimental layout. B) Clustergram of transcriptomes of biopsies (purple) and fecal washes (yellow). C) Principal component analysis (PCA) of biopsies (purple) and fecal washes (yellow). Black circles highlight inflamed samples. D) Spearman correlations between the transcriptomes of pairs of either biopsies or fecal washes that are both annotated as inflamed and mixed pairs (one annotated as inflamed and the other not). (A) Created with BioRender.com. TI – terminal ileum, P – proximal colon, D – distal colon. Conclusion: Our study establishes the power of colonic fecal washes for identifying pathological processes throughout the ileal-colonic axis.